Technological Tool for Formative Assessment in Higher Education: ZipGrade - Arora, Bani; Al-Hattami, Abdulghani (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2024)
This descriptive study examines the effectiveness of ZipGrade, a digital assessment tool, in the context of formative evaluations within classroom settings, focusing on its deployment for multiple-choice question quizzes. This research contributes to the dialogue on the integration of information and communication technology to promote quality education and address the literature gap in providing immediate feedback to enhance the learning outcomes. Drawing on a sample of 63 fourth year B.Ed. students in Bahrain, the study combines quantitative and qualitative methodologies to assess student perceptions about the utility and effectiveness of ZipGrade. Data were collected through a semi-structured questionnaire following the administration of a series of formative tests across selected course segments. The findings reveal a predominantly positive reception of ZipGrade among students, highlighting its ease of use, immediate feedback provision, and potential to more effectively engage learners in the assessment process. Challenges such as the necessity for physical printing of answer sheets, a predisposition towards multiple-choice questions, and infrastructural and policy-related barriers were identified, suggesting areas for further development and support.